Synthesis of Ideas and Creative Design - Amos I.T. Chang (Oz, 1979)
A workshop presentation of a design thought model and an organic Design Process. ACSA 1975 west central regional conference Nov. 20-22 Allerton House-Urbana-Champaign, ILLINOIS